Perception of Green Technology Among TVET Professional in Pakistan - Rajput, Abdul Ghani; Akhtar, Muhammad Naeem; Akram, Muhammad Nadeem (Journal of Technical and Vocational Education and Training, 2021)
Green technology concept is increasing in Pakistan. The objective of green technology is to make clean environment and sustain biodiversity. The increasing implication of sustainability is having a key impact on business industry and association, as well as society as a whole. Hence, readiness of the forthcoming workforce for the coming green economy is a challenging task for Technical Vocational Education and Training authorities in Pakistan. Hence, the objective of this research was to identify the perception of TVET professional in Pakistan. A sample of 30 TVET professional across Pakistan was randomly selected. The research identified that most of the TVET professional statement that their perception of green technology is relatively high, the use of green technology application is moderate. daily application of green technology in their lives is only moderate. Interestingly, in the open-ended section, TVET professionals were asked to state an example of a greening TVET, 35% of the respondents admitted that they do not know. Further, almost half of the respondents state that greening elements are included in different TVET programs curriculum.